2014
DOI: 10.1155/2014/560962
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Nanoparticles for the Delivery of Gemcitabine Hydrochloride

Abstract: Gemcitabine (2,2-difluorodeoxycytidine) is a deoxycytidine analog, currently being used as a first-choice drug in pancreatic metastatic cancer. Gemcitabine is administered weekly as 30-minute infusion with starting dose ranging from 800 to 1250 mg/m2. The aim of the present work was to develop starch nanoparticles (NPs) for the delivery of gemcitabine hydrochloride that could reduce its dose related side effects and may prolong its retention time (24 hrs) for the treatment of pancreatic cancer. Nanoparticles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…Our results are in agreement with earlier reports on nanostarch from cassava and curcumin loaded starch nanoparticles . In an earlier study, gemcitabine hydrochloride loaded corn starch nanoparticles were also reported to have similar morphology . The morphological characteristics of cassava starch nanoparticles were found to be similar to that of waxy maize starch nanoparticles prepared by Angellier et al and pea starch nanoparticles prepared by Chen et al .…”
Section: Resultssupporting
confidence: 92%
“…Our results are in agreement with earlier reports on nanostarch from cassava and curcumin loaded starch nanoparticles . In an earlier study, gemcitabine hydrochloride loaded corn starch nanoparticles were also reported to have similar morphology . The morphological characteristics of cassava starch nanoparticles were found to be similar to that of waxy maize starch nanoparticles prepared by Angellier et al and pea starch nanoparticles prepared by Chen et al .…”
Section: Resultssupporting
confidence: 92%
“…Reaction yield (RY) of the synthesized chitosan–hexaconazole nanoparticles was calculated using Equation 6 [51].…”
Section: Methodsmentioning
confidence: 99%
“…The reaction yield of the synthesized nanoparticles was calculated using Equation 7 [36]: RY = [Produced nanoparticle (mg)/(used chitosan (mg) + used dazomet (mg))] × 100…”
Section: Methodsmentioning
confidence: 99%